Integrating AI & IT Security in Front Office Systems: Enhancing Guest Experience While Protecting Privacy - Pandirkar , Aarti; Mhaske , Kishor; Mankame , Sameer; Singh , Punam; Patil, Pratik; D'souza , Lenwin; Niklankar, Alpana (Journal of Neonatal Surgery, 2025)
The hospitality business is quickly going online and, therefore, application of Artificial Intelligence (AI) and sophisticated Information Technology (IT) security software has significantly reshaped the work of the front office. The front office systems have gained great significance as the process of making services personalized to the guests, smooth check-in and check-out, intelligent communication with the guest and decision-making based on data is streamlined. However, the increased consumption of digital spaces and technologies, based on artificial intelligence, has become an object of fear regarding privacy of the data and cybercrimes, and the subject of ethical and adequate use of the data provided by the guest. In this paper, the integration of AI and IT security into the front office systems is going to be examined considering the dual purpose of improving the quality of the offered services and ensuring the sound security of highly sensitive information of the guests. The paper defines the way AI-based applications such as chatbots, facial recognition, predictive analytics, and automated customer relationship management systems ensure efficiency, alongside the guest satisfaction. Simultaneously, it also examines the following IT security measures as the encryptions, the control of access, the detection of intruders, compliance with data safeguarding regulations, and the safe network infrastructure. It is important to note that the research shows the importance of making sure that technological innovation is well coordinated through adequate cybersecurity frameworks through the analysis of current practices and challenges. The paper concludes that harmonious fusion of AI and IT security, not only leads to the rise in trust and loyalty among the guests with both, but also ensures the sustainability of the digital transformation in the practices of the hospitality front office.